2015
DOI: 10.1097/md.0000000000001729
|View full text |Cite
|
Sign up to set email alerts
|

Red and Processed Meat Consumption Increases Risk for Non-Hodgkin Lymphoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The flow chart for the selection of eligible studies is shown in Figure 1. The Newcastle‐Ottawa Scale (NOS) score of the selected articles was 7‐8, which indicated that the quality of all eligible studies was relatively high 51 . Seven of the studies involved Caucasian participants, 29,31,32,44,46,48,49 and five 28,40‐43 involved mixed‐race participants, while thirteen involved Asian participants 26,27,30,33‐39,45,47,50 .…”
Section: Resultsmentioning
confidence: 99%
“…The flow chart for the selection of eligible studies is shown in Figure 1. The Newcastle‐Ottawa Scale (NOS) score of the selected articles was 7‐8, which indicated that the quality of all eligible studies was relatively high 51 . Seven of the studies involved Caucasian participants, 29,31,32,44,46,48,49 and five 28,40‐43 involved mixed‐race participants, while thirteen involved Asian participants 26,27,30,33‐39,45,47,50 .…”
Section: Resultsmentioning
confidence: 99%
“…The AMSTAR item number 8 referred to whether the scientific quality grading was used appropriately in formulating conclusions, i.e. describing the quality of the evidence [35], and only 5 out of 22 systematic reviews fulfilled that [30,33,34,39,40]. All reviews assessed publication bias, when applicable, and overall there were no indication of such bias, regardless of test, except in three reviews (on hepatocellular carcinoma [32], gastric cancer [41] and cancer mortality [33] that all favored significant results ( Tables 6 and 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The two systematic reviews reached different conclusions: the meta-analysis by Solimini et al found no association [36], while the meta-analysis by Yang et al suggested a direct association with risk of Non-Hodgkin lymphoma (RR: 1.17; 95% CI: 1.07, 1.29 for high vs. low processed meat intake) [40]. The meta-analyses from the two reviews included the same 3 cohort studies but the case-control studies differed; out of a total of 14 case-control studies, Solimini et al included 8 case-control studies and Yang et al included 13 case-control studies; only 7 case-control studies overlapped between the two reviews.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to liver, colon and prostate, some HAA induce cancer in lymphoid tissue and the hematopoietic system in rodents [Sugimura et al, 2004]. Some epidemiological studies have reported that a high intake of red meat is associated with an increased risk in colon and prostate cancers, but also for the development of lymphoma cancer [Zheng and Lee, 2009;John et al, 2011;Ferrucci et al, 2012;Yang et al, 2015].…”
Section: Introductionmentioning
confidence: 99%